The impact of hand proportions on tool grip abilities in humans, great apes and fossil hominins: A biomechanical analysis using musculoskeletal simulation. Issue 125 (December 2018) - Bardo, Ameline; Vigouroux, Laurent; Kivell, Tracy L.; Pouydebat, Emmanuelle
Abstract: Differences in grip techniques used across primates are usually attributed to variation in thumb-finger proportions and muscular anatomy of the hand. However, this cause-effect relationship is not fully understood because little is known about the biomechanical functioning and mechanical loads (e.g., muscle or joint forces) of the non-human primate hand compared to that of humans during object manipulation. This study aims to understand the importance of hand proportions on the use of different grip strategies used by humans, extant great apes (bonobos, gorillas and orangutans) and, potentially, fossil hominins ( Homo naledi and Australopithecus sediba ) using a musculoskeletal model of the hand. Results show that certain grips are more challenging for some species, particularly orangutans, than others, such that they require stronger muscle forces for a given range of motion. Assuming a human-like range of motion at each hand joint, simulation results show that H. naledi and A. sediba had the biomechanical potential to use the grip techniques considered important for stone tool-related behaviors in humans. These musculoskeletal simulation results shed light on the functional consequences of the different hand proportions among extant and extinct hominids and the different manipulative abilities found in humans and great apes.